2012
DOI: 10.1584/jpestics.d11-009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dieldrin uptake in cucumber fruits and methanol–water extractable residue in soil

Abstract: We investigated the relationship between dieldrin concentrations in soil samples extracted with a 50% (v/v) methanol-water solution and dieldrin concentrations in four cultivars of cucumber fruits grown in 12 elds. Regression analysis showed signicant (p<0.01) relationships between dieldrin concentrations in soil samples extracted with a 50% (v/v) methanol-water solution and dieldrin concentrations in four cultivars of cucumber fruits. Varietal di erences were re ected in the slope of the regression lines. e f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…6). A similar trend was confirmed in the case of dieldrin in the early-growth cucumber shoots (R 2 =0.966) 15) and fruits (R 2 =0.286 to 0.460) 16) , and it was considered that the difference in the cultivation season influ- Table 4 Nodal position, fresh weight (g FW) and dry matter production (%) of pumpkin enced the uptake of dieldrin by cucumber 16) . However, the pumpkin cultivation season is the same in this study.…”
Section: Relationship Between Hepx Concentrations In Soils Extracted supporting
confidence: 62%
See 1 more Smart Citation
“…6). A similar trend was confirmed in the case of dieldrin in the early-growth cucumber shoots (R 2 =0.966) 15) and fruits (R 2 =0.286 to 0.460) 16) , and it was considered that the difference in the cultivation season influ- Table 4 Nodal position, fresh weight (g FW) and dry matter production (%) of pumpkin enced the uptake of dieldrin by cucumber 16) . However, the pumpkin cultivation season is the same in this study.…”
Section: Relationship Between Hepx Concentrations In Soils Extracted supporting
confidence: 62%
“…Sakai et al 15) found a negative correlation between the SOC and bioconcentration factor (BCF), which was calculated as the dieldrin concentration in the cucumber shoot divided by the exhaustive soil concentration obtained from Soxhlet extraction with acetone for 16 h. These reports indicated that the availability of POPs for plants cannot be explained by the exhaustive extraction of soil with different SOCs. In our previous studies, it was found that non-exhaustive soil extraction using 50% (v/v) methanol-water solution can be used to determine the availability for dieldrin residue in early-growth cucumber shoots 15) and fruits 16) . However, compounds differ between dieldrin and HEPX, and dieldrin uptake abilities among 11 cucurbits differed by about 10 times 8) .…”
mentioning
confidence: 99%
“…Although they did not examine the root zones of plants, their results imply that the vertical distribution of roots in soil, especially in a narrow depth range, affects the amount of chemicals taken up in plants. Previous studies suggest that plant uptake of organic chemicals is influenced by various factors such as pesticide chemical properties, soil type, ,, plant species, , plant growing conditions, , and growth stage. , However, the influence of the vertical distribution of pesticides in soils on plant uptake has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%